DETERMINANTS OF UNSAFE ACTION IN WORKERS PRODUCTION DEPARTEMENT AT PT KOKOH SEMESTA CIKANDE - Sadya Bustomi (Journal of Industrial Engineering & Management Research, 2023)
The International Labor Organization (ILO) says that as many as 2.3 million deaths are caused by disease or work-related accidents that occur each year. This study aims to determine the factors associated with unsafe actions in production workers at PT. Sturdy Universe Cikande Serang Banten. type of research used is quantitative research with analytic observational method with cross sectional design. The number of respondents in this study were 60 respondents. The sampling technique used proportional sampling with univariate and bivariate analysis using the Chi Square test. The results of this study showed that as many as 21 (35%) respondents took safe actions, as many as 15 (25%) respondents had good knowledge, as many as 31 (51.6%) respondents had good attitudes and as many as 28 (46.6%) respondents had work 6-10 years. The results of the bivariate analysis test showed that there was a relationship between knowledge (Pvalue = 0.000), attitude (Pvalue = 0.003) and years of service (Pvalue = 0.012) with unsafe actions.